Environmental justice in India: a case study of environmental impact assessment, community engagement and public interest litigation. Issue 1 (2nd January 2020) - Dilay, Ariane; Diduck, Alan P.; Patel, Kirit
ABSTRACT: This paper scrutinizes environmental impact assessment (EIA) in India and its potential environmental justice implications. We focused on procedural aspects of environmental justice and concentrated specifically on public interest litigation. Using a qualitative case study (document review, semi-structured interviews, participant observation, transect walks, thematic analysis), we examined conflict and litigation in an EIA of a proposed industrial development affecting a wetland and agricultural livelihoods in the state of Gujarat. The study 1) describes aspects of the EIA that triggered opposition, including litigation before the National Green Tribunal (NGT), 2) explains the extent to which the EIA addressed concerns of potentially affected local communities, and 3) assesses the effectiveness of the court system and the NGT in resolving disputes arising from the EIA. We found: that important gaps in the EIA report and lack of public participation opportunities were important triggers for litigation; crucial disconnects between issues addressed in the EIA and concerns of affected communities; and formidable challenges to gaining full access to legal representation, technical expertise and judicial remedies. Addressing these shortcomings would improve the EIA regime, enhance procedural aspects of environmental justice in India, and improve the prospects for distributive, recognitional and restorative justice by ensuring that EIAs reflect local knowledge, values and aspirations.